Intention and motivation to pursue higher education among registered nurses and midwives: a cross-sectional study during COVID-19 - Abdulqadir J. Nashwan (14586036) (2022)
Objectives To determine the intention and motivation of nurses and midwives to pursue their higher education considering several factors. Methods This is a cross-sectional study were a 16-item online survey was distributed using a convenience sampling method to approximately 12,000 nurses and midwives between May – July 2021. Results A total of 513 eligible nurses and midwives participated in the study. Most of the respondents were females (76.61%), with a bachelor’s degree (72.3%) and well experienced (11–15 years) (35.4%). Most nurses and midwives are highly motivated to pursue higher education (79.14%). The most motivating factor for the respondents is their professional goals (85.2%), While the most dissuading factor was the cost. Regarding COVID-19, about 28% of the respondents said that the COVID-19 pandemic has a negative effect on their desire to go for higher education. Conclusions The nurses and midwives were highly motivated to pursue higher education regardless of their demographic status, available resources, and barriers. Furthermore, the eagerness of the nurses and midwives to pursue higher education, which is rooted in their desire to grow in their profession. Other information  Published in: International Journal of Nursing Education Scholarship License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1515/ijnes-2021-0152